The Mediating Effect of Budget Pressure on Behavioral Declaration of Audit - Edwin Setiawan; Andreas Andreas; Novita Indrawati; Hardi Hardi (JAFFA, 2019)
This study aims to test and analyze the behavior of audit quality deterioration by integrating the characteristics of individual auditors (locus of control and organizational commitment) with time budget pressure. The study was conducted by survey method by distributing questionnaires to auditors who worked at KAP in the Provinces of West Sumatra, Riau and Riau Islands. The sampling technique uses the purpose sampling method. The questionnaire that can be used totaling 60 questionnaires. Data analysis using wrapPLS 6.0. The results showed that internal locus of control had a negative effect on time budget pressure and decreased audit quality behavior, external locus of control had a positive effect on time budget pressure and decreased audit quality behavior, organizational commitment negatively affected time budget pressure and decreased audit quality behavior, and time budget pressure has a positive effect on audit quality deterioration behavior, and time budget pressure mediates the influence of locus of control, organizational commitment to audit quality deterioration.